Pengaruh Model Problem Based Learning (PBL) terhadap Kemampuan Membangun Sikap Mandiri dan Hasil Belajar Siswa Pada Mata Pelajaran PKn Kelas IV SD Negeri 75 Kota Bengkulu - DENTY HARMELIA; Puspa Djuwita (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2022)
// This study aims to determine the effect of the Problem Based Learning model on the ability to build independent attitudes and student learning outcomes in the fourth grade Pkn Subject SD Negeri 75 Kota Bengkulu. This type of research is the Mix Method. The research samples obtained were students of grade IV A and IV D SD Negeri 75 Bengkulu City, amounting to 38 and 37 students. The research instruments used were questionnaire sheets, interview sheets and test sheets. The research data on the independent attitude showed that the result of t count was 1.746 with a significant level of 5%, namely 0.020 <0.05, meaning that there was an influence of the PBL model on the independent attitude of students in class IV SD Negeri 75 Bengkulu City. In the results of the pretest value in the experimental class and control class, namely t count of 1.528 with a significant level of 5%, namely 0.058> 0.05, it means that there is no influence of the PBL model on the independent attitude of students in class IV SD Negeri 75 Bengkulu City. Whereas the results of the posstest score in the experimental class and control class obtained t count of 3.345 with a significant level of 5%, namely 0.001 <0.05, meaning that there is an effect of the PBL model on the independent attitude of students in class IV SD Negeri 75 Bengkulu City so it can be concluded that PBL model on the ability of independent attitudes and learning outcomes of fourth grade students of SD Negeri 75 Kota Bengkulu.